Redox Potential Studies Based on Scan-Rate Analysis of the Diffusional Control and Dft Calculations of the Schiff Base [(E)-4-Amino-3-((3,5-Di-Tert-Butyl-2-Hydroxybenzylidene)Amino) Benzoic Acid] - Morales-Guevara, R; Morales-Guevara, R (Sociedade Brasileira de Quimica, 2025)
Schiff bases are diverse organic compounds with an azomethine structure (–C=N–), holding potential in both chemistry and biology. They serve as catalysts, stabilizers, and exhibit various biological activities. The molecular structure of Schiff bases influences their biological properties, including antimicrobial effects. Redox-active compounds with more negative potentials tend to be more effective against microbes. In one of our recent studies, we explored the antimicrobial properties of two Schiff bases derivatives, SB-1 ((E)-4-amino-3-((3,5-di-tert-butyl-2-hydroxybenzylidene)amino) and SB-2 ((E)-2-((4-nitrobenzilidene)amino)aniline). SB-1 showed antibacterial activity against certain Gram-positive bacteria, while SB-2 did not. The difference in their cyclic voltametric profiles, especially SB-1’s more negative reduction potential, prompted us to carry out further characterizations, including scan-rate studies, solvent analysis, and computational calculations. We found that SB-1, which presents a stable intramolecular hydrogen bond, undergoes irreversible oxidation, likely at the –NH2 group, and a quasi-reversible reduction via an intramolecular reductive coupling of the (–C=N–) azomethine group, supported by orbital theoretical calculations. This research sheds light on the potential applications of Schiff bases in antimicrobial contexts, guided by their redox properties and structure. © 2025 Sociedade Brasileira de Quimica. All rights reserved.